2021
DOI: 10.1007/978-3-030-85577-2_97
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of FAHP with Type-1 and Interval Type-2 Fuzzy Sets for ICT Implementation in Smart Cities

Abstract: In Type-1 Fuzzy Sets (T1FS), membership functions have not associated with uncertainty. Type-2 Fuzzy Sets (T2FS) provides an opportunity to incorporate the uncertainty of membership functions into the theory of fuzzy sets at the expense of the number of additional computational operations. Therefore, Interval Type-2 Fuzzy Sets (IT2FS) is introduced where the number of computational operations is reduced to T2FS while preserving the good properties that T2FS possesses. This paper presents a comparative study of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…A variety of major phonic disturbance metrics, comprising 339 features with varying audio signal properties have been observed as a result. A comparative study of T1FS and IT2FS with fuzzy AHP presented by Milošević et al (2021) . It has been shown that membership functions are related to uncertainty within type-1 fuzzy sets; thus, type-2 fuzzy sets provide a chance to incorporate membership value uncertainty in fuzzy set theory even at the price of an increased number of extra computing processes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A variety of major phonic disturbance metrics, comprising 339 features with varying audio signal properties have been observed as a result. A comparative study of T1FS and IT2FS with fuzzy AHP presented by Milošević et al (2021) . It has been shown that membership functions are related to uncertainty within type-1 fuzzy sets; thus, type-2 fuzzy sets provide a chance to incorporate membership value uncertainty in fuzzy set theory even at the price of an increased number of extra computing processes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Strenuous changes in city life, which occur daily, have prompted us to consider ways to build a more sustainable society that can withstand the rapid development of our environment [6]. Through the use of data sensors, public platforms for e-government and e-commerce, the ongoing development of traffic, the digitization of cultural heritage, and virtual tours, cutting-edge technologies based on big data, Internet of Things platforms, and remote sensing images have become part of people's everyday lives in modern and advanced urban infrastructure [7,8]. The new Building Management System (BMS) will significantly contribute to the market's growth through the proliferation of the Internet of Things (IoT), Artificial Intelligence (AI), Virtual Reality (VR), and Business Information Modeling (BIM).…”
Section: Introductionmentioning
confidence: 99%